The Effectiveness of English Sholawat Song As Media on Students’ Motivation in Speaking Comprehension - Khudriyah Khudriyah; M. Fahmy Almuwallid; Julianne Kamelia Riza (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Motivation plays a crucial role in achieving various objectives across economic, religious, educational, and linguistic domains. This study specifically examined whether sholawat songs—Islamic devotional songs—influence students' motivation to learn speaking. Employing a quantitative research methodology, the researcher collected data through questionnaires distributed to participants. Subsequently, the data underwent analysis using simple linear regression to determine the relationship between the two variables. The research findings demonstrated that sholawat songs effectively enhance students' motivation for speaking learning. The statistical analysis revealed significant results through multiple measures. When comparing the t-counted value with the t-table value, the result (3.463 > 2.045) indicated statistical significance. Similarly, the p-value analysis (0.002 < 0.05) further confirmed the significance of the regression coefficient. These results collectively demonstrate that the relationship between sholawat songs and speaking motivation is statistically meaningful and not merely due to chance. Therefore, incorporating sholawat songs into language learning curricula may effectively boost student engagement and motivation in developing speaking skills